Strategic Problems of the Far East of Russia - Sergey Mikhailovich Darkin (Управленческое консультирование, 2018)
The article provides an overview of premises and features for working out an economic and social development strategy voiced during the SPIEF 2015 panel session. The article contains a case study of the Primorsky Region development strategy and its successful implementation as a development model. The main focus is placed on assessing natural, human, technological, scientific and financial resources limitations in a particular region. Current problems and possible perspectives for implementing public-private partnership mechanisms in Russia and the Far East Federal District are determined in the article with reference to the experience of developed countries. Aquaculture as a sector of the fishing industry and its current development features are also under scrutiny in this research being strategically important for the Far East Region.